Implementation of Community Service in Providing Support for Children's Growth and Development - Pipin Angela; Adlina Nur Rohmah; Salmah Ayu Andini; Titin Sunaryati (JOURNAL INCLUSIVE SOCIETY COMMUNITY SERVIES, 2024)
This community service program was carried out at Rumah Pelangi, Sukawangi District, Bekasi Regency. Some of the main problems that are a problem in Binong Village, Jatireja Village, East Cikarang District, Bekasi Regency, are the lack of optimal knowledge of access to traffic signs and roads. The results of this PKM activity are described through the role of the community in providing positive reinforcement in the form of support and appreciation to children. The process of strengthening children here is through the concept of playing and learning and providing the necessary facilities and infrastructure